2017
DOI: 10.1075/jlp.15037.sel
|View full text |Cite
|
Sign up to set email alerts
|

Linguistic landscape of Gezi Park protests in Turkey

Abstract: Gezi Park protests that rocked Turkey in 2013 left a significant mark in the country’s collective memory and contributed to the construction of a new language of political resistance. To challenge an increasingly authoritarian government, the protesters used novel repertoires of contention, particularly political graffiti. To better understand different types of linguistic and symbolic communication tools used in the public space during Gezi Park protests and their impact on different set of audiences, this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 12 publications
0
7
0
1
Order By: Relevance
“…Karlander (2019) closely examined those anti-graffiti regimes and found that the acts of graffiti erasure often left visible traces behind, which he related to issues of the semiotics of non-existence. Another angle was taken by Seloni and Sarfati (2017), who analyzed graffiti during the Gezi Park protests in Istanbul in the summer of 2013. They found that the graffiti combined and mixed Turkish and English in creative hybrid forms.…”
Section: Graffitimentioning
confidence: 99%
“…Karlander (2019) closely examined those anti-graffiti regimes and found that the acts of graffiti erasure often left visible traces behind, which he related to issues of the semiotics of non-existence. Another angle was taken by Seloni and Sarfati (2017), who analyzed graffiti during the Gezi Park protests in Istanbul in the summer of 2013. They found that the graffiti combined and mixed Turkish and English in creative hybrid forms.…”
Section: Graffitimentioning
confidence: 99%
“…In comparison to other art forms, graffiti had a powerful presence for its all-round visibility and physical scale. Seloni & Sarfati (2017) documented and analysed the usage of street art and graffiti from the Gezi Park episode in Istanbul during 2013. A creative use of this art form and technique helped galvanize the protesters who were resisting a government move to convert a segment of historic urban landscape into a commercial space.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Interfering in the appearance of property, damaging, disfiguring, spoiling, writing, affixing material or performing any such act which results in loss of aesthetics is categorized as defacement (Government of Sindh, 2014). This enterprise is also defined as transgressive, as it is done in defiance of standing laws but often with objectives to benefit a public cause (Seloni and Sarfati, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…And indeed, research on resistance has focused on movements such as the Arab Spring (Elyachar & Winegar, 2012), political movements in different countries (Idle & Nunns, 2011;Lazar, 2017;Seloni & Sarfati, 2017;Sinatora, 2019), antiausterity protests (Theodossopoulos, 2013), occupy movements (Hickel, 2012;Martin Rojo, 2014;Razsa & Kurnik, 2012) or actions by specific ethnic groups (Mpofu, 2018;Chibuwe & Ureke, 2016). Recently there has also been some investigation of how media discourses articulate resistance to anti-immigrant and antihumanitarian sentiments (Balabanova & Trandafoiu, 2020).…”
Section: Conceptualizing Resistancementioning
confidence: 99%